HIV Latency-Reversing Agents Have Diverse Effects on Natural Killer Cell Function - Garrido, Carolina; Spivak, Adam M.; Soriano-Sarabia, Natalia; Checkley, Mary Ann; Barker, Edward; Karn, Jonathan; Planelles, Vicente; Margolis, David M. (Frontiers in Immunology, 2016)
In an effort to clear persistent HIV infection, and achieve a durable therapy-free remission of HIV disease, extensive pre-clinical studies and early pilot clinical trials are underway to develop and test agents that can reverse latent HIV infection and present viral antigen to the immune system for clearance. It is therefore critical to understand the impact of latency reversing agents (LRAs) on the function of immune effectors needed to clear infected cells. We assessed the impact of LRAs on the function of natural killer (NK) cells, the main effector cells of the innate immune system. We studied the effects of three histone deacetylase inhibitors (SAHA or vorinostat, romidepsin and panobinostat) and two protein kinase C (PKC) agonists (prostratin and ingenol) on the antiviral activity, cytotoxicity, cytokine secretion, phenotype and viability of primary NK cells. We found that ex vivo exposure to vorinostat had minimal impact on all parameters assessed, while panobinostat caused a decrease in NK cell viability, antiviral activity and cytotoxicity. Prostratin caused NK cell activation and interestingly, improved antiviral activity. Overall, we found that LRAs can alter the function and fate of NK cells, and these effects must be carefully considered as strategies are developed to clear persistent HIV infection.